A powder coating and its preparation method and application
By using MN and Zn in pink coatings to mix copper-molybdenonate and KH-550 modified molybdenum sulfurization in powder coatings, the existing antibacterial powder coatings precious metal antibacterial antibacterial antibacterial antibacterial antibacterial agent is expensive and does not last long, and achieved significant antibacterial performance And mechanical performance improvement.
Patent Information
- Application Number
- CN202411178652.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-08-27
AI Technical Summary
The existing antibacterial powder coatings have the problem that precious metal antibacterial agents are expensive and do not last long enough, and it is difficult to meet the actual production needs.
By adding Mn and Zn co-doped copper molybdate and KH-550 modified molybdenum sulfide to the powder coating, the antibacterial properties and mechanical properties are improved.
It significantly improves the antibacterial and mechanical properties of powder coatings, provides excellent anti -bacterial effect and enhanced physical properties.
Smart Images

Figure BDA0005011450680000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of powder coatings, and more specifically, relates to a powder coating and a preparation method and application thereof. Background Art
[0002] Powder coating is a kind of coating in powder form that does not use solvents in the production and application process. Compared with traditional solvent-based coatings, powder coatings have the advantages of zero pollution emissions, convenient transportation, simple preparation process, excellent coating performance, and high utilization rate. In addition, due to the environmental and economic advantages of powder coatings, it has good development potential. Powder coatings are widely used in food, health care, and hygiene. Since they need to come into contact with people, these industries have extremely high requirements for the antibacterial properties of coatings, so the demand for antibacterial properties is increasing. However, the quality of antibacterial coatings on the market is uneven, so it is very important to develop a powder coating that is non-toxic and has excellent antibacterial properties.
[0003] CN117165168A discloses a nano self-cleaning powder coating and a preparation method thereof. The nano self-cleaning powder coating provided by the present invention comprises: fluorine-containing terminal hydroxyl polyester resin, isocyanate, nano silver ion antibacterial agent, hydrophobic nano silicon dioxide, rutile nano titanium dioxide, filler, leveling agent, and dispersant. The nano self-cleaning powder coating has excellent hydrophobic and oleophobic effects, can resist water-based dirt and oily dirt, and has the effects of high adhesion and high impact resistance.
[0004] CN118185434A discloses a weather-resistant powder coating and a preparation method thereof. The powder coating of the invention comprises the following raw materials in parts by weight: 40-50 parts of polyester resin, 20-30 parts of modified acrylic resin, 0.5-2 parts of antioxidant, 5-10 parts of reinforcing filler, 2-5 parts of curing agent, 0.3-0.8 parts of leveling agent, and 0.2-0.5 parts of stabilizer; the coating is based on polyester resin, and various additives are added to play a synergistic role, thereby improving the weather resistance of the coating, wherein the addition of reinforcing filler improves the UV resistance and hydrophobicity of the coating; the addition of modified acrylic resin improves the antibacterial property and corrosion resistance of the coating.
[0005] CN118109104A discloses a plasma powder coating with antibacterial function and a preparation method thereof. The plasma powder coating with antibacterial function comprises the following raw materials in parts by weight: 15-22 parts of epoxy resin, 5-11 parts of polyester resin, 3-9 parts of curing agent, 5-9 parts of leveling agent, 6-12 parts of defoaming agent, 13-18 parts of filler, 15-21 parts of vanillin and 9-20 parts of phytic acid. After comparison, it is shown that the combination of all raw materials of the plasma powder coating with antibacterial function can inhibit bacterial growth, and the combined effect of vanillin and phytic acid has a better inhibitory effect on bacterial reproduction.
[0006] The existing technology achieves antibacterial effect by adding precious metal Ag or organic antibacterial agents, but the precious metal antibacterial agents are expensive or do not last long enough and cannot meet the needs of actual production. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art, and to provide a powder coating and its preparation method and application. In parts by weight, it includes the following components: 120-160 parts of polyester resin, 20-40 parts of epoxy resin E12, 2-6 parts of curing agent, 0.5-1.5 parts of benzoin, 2-4 parts of leveling agent, 3-7 parts of copper molybdate co-doped with Mn and Zn, and 1-5 parts of molybdenum sulfide modified with KH-550. The present invention improves not only the antibacterial properties of the powder coating, but also the mechanical properties of the powder coating by adding copper molybdate co-doped with Mn and Zn and molybdenum sulfide modified with KH-550 to the powder coating.
[0008] The object of the present invention is to provide a powder coating.
[0009] Another object of the present invention is to provide a method for preparing the powder coating.
[0010] Another object of the present invention is to provide an application of the powder coating.
[0011] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0012] A powder coating, comprising the following components in parts by weight:
[0013] 120-160 parts of polyester resin;
[0014] Epoxy resin E12 20-40 parts;
[0015] 2 to 6 parts of curing agent;
[0016] 0.5-1.5 parts of benzoin;
[0017] 2 to 4 parts of leveling agent;
[0018] Mn and Zn co-doped copper molybdate 3 to 7 parts;
[0019] 1 to 5 parts of KH-550 modified molybdenum sulfide.
[0020] In the present invention, the preferred technical solution is that the preparation method of the KH-550 modified molybdenum sulfide comprises the following steps:
[0021] The molybdenum source and thiourea are dissolved in deionized water, and stirred evenly to obtain a mixed solution; then a hydrothermal reaction is carried out, and the mixture is washed and vacuum dried to obtain molybdenum sulfide; the molybdenum sulfide and KH-550 are ultrasonically dispersed in deionized water, and reacted at 50 to 80° C. for 2 to 4 hours to obtain KH-550-modified molybdenum sulfide.
[0022] Preferably, the molybdenum source includes at least one of sodium molybdate, potassium molybdate or ammonium molybdate; the molar ratio of the molybdenum source to thiourea is 1:3-5; and the mass ratio of the molybdenum sulfide to KH-550 is 100:5-15.
[0023] Preferably, the hydrothermal reaction conditions are 160-240° C. for 15-30 h, and the vacuum drying is 60-90° C. for 8-12 h.
[0024] In the present invention, a preferred technical solution is that the preparation method of Mn and Zn co-doped copper molybdate comprises the following steps:
[0025] Manganese salt, zinc salt, copper salt and ammonium molybdate are ultrasonically dispersed in deionized water to obtain a dispersion, and then a sodium hydroxide solution with a concentration of 0.5 mol / L is added dropwise to adjust the pH of the dispersion to 9, and then a hydrothermal reaction is carried out, filtered, washed, and dried to obtain Mn and Zn co-doped copper molybdate.
[0026] Preferably, the manganese salt is one of manganese nitrate, manganese chloride, and manganese acetate; the zinc salt is one of zinc nitrate, zinc chloride, and zinc acetate; the copper salt is one of copper nitrate, copper chloride, and copper acetate; the molar ratio of the manganese salt, zinc salt, copper salt, and ammonium molybdate is: x:y:(1-xy):1-3; x=0.02-0.04:; y=0.01-0.03.
[0027] Preferably, the hydrothermal reaction is carried out at 140-160° C. for 4-6 hours, and the drying is carried out at 90-110° C. for 10-18 hours.
[0028] In the present invention, the preferred technical solution is that the polyester resin is SJ4868 polyester resin; the curing agent is adipic acid dihydrazide; and the leveling agent is BYK-368P.
[0029] Based on the above-mentioned method for preparing a powder coating, the preparation method comprises the following steps:
[0030] The raw materials are mixed to obtain a mixed material, which is then melt-extruded, tableted and crushed through a twin-screw extruder, and then pulverized and sieved to obtain a powder coating; the temperature of the first zone of the twin-screw extruder is 100° C., the temperature of the second zone is 125° C., the temperature of the third zone is 115° C., and the screw speed is 50 r / min.
[0031] Based on the above-mentioned application of a powder coating in the field of food, medical care or hygiene.
[0032] The present invention has the following beneficial effects:
[0033] The present invention improves the antibacterial property of copper molybdate itself by co-doping copper molybdate with Mn and Zn, and the obtained powder can improve the mechanical properties of powder coatings. The molybdenum sulfide modified by KH-550 not only improves the dispersibility of molybdenum sulfide in powder coatings, but also increases the bonding strength between molybdenum sulfide and the matrix material, thereby improving the mechanical properties of the powder. That is, the powder coating of the present invention has excellent antibacterial properties and mechanical properties. DETAILED DESCRIPTION
[0034] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0035] The polyester resin is SJ4868 polyester resin; the curing agent is adipic acid dihydrazide; and the leveling agent is BYK-368P.
[0036] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0037] Example 1
[0038] A powder coating, comprising the following components in parts by weight:
[0039] 140 parts of polyester resin,
[0040] Epoxy resin E12 30 parts;
[0041] 4 parts of curing agent,
[0042] 1 part benzoin,
[0043] 3 parts of leveling agent,
[0044] Mn and Zn co-doped copper molybdate 5 parts;
[0045] 3 parts of KH-550 modified molybdenum sulfide;
[0046] The preparation method of the KH-550 modified molybdenum sulfide comprises the following steps:
[0047] Dissolve 1 mol of ammonium molybdate and 4 mol of thiourea in 200 mL of deionized water and stir to obtain a mixed solution; then hydrothermally react at 200°C for 20 hours, wash, and vacuum dry at 80°C for 10 hours to obtain molybdenum sulfide; ultrasonically disperse 100 g of molybdenum sulfide and 10 g of KH-550 in 250 mL of deionized water, and react at 70°C for 3 hours to obtain KH-550-modified molybdenum sulfide.
[0048] The preparation method of Mn and Zn co-doped copper molybdate comprises the following steps:
[0049] 0.03 mol manganese nitrate, 0.02 mol zinc chloride, 0.95 mol copper acetate and 2 mol ammonium molybdate were ultrasonically dispersed in 150 mL of deionized water to obtain a dispersion, and then a 0.5 mol / L sodium hydroxide solution was added dropwise to adjust the pH of the dispersion to 9, and then hydrothermally reacted at 150° C. for 5 h, filtered, washed, and dried at 100° C. for 14 h to obtain Mn and Zn co-doped copper molybdate.
[0050] A method for preparing a powder coating, the method comprising the following steps:
[0051] The raw materials are mixed to obtain a mixed material, which is then melt-extruded, tableted and crushed through a twin-screw extruder, and then pulverized and sieved to obtain a powder coating; the temperature of the first zone of the twin-screw extruder is 100° C., the temperature of the second zone is 125° C., the temperature of the third zone is 115° C., and the screw speed is 50 r / min.
[0052] Example 2
[0053] A powder coating, comprising the following components in parts by weight:
[0054] 160 parts of polyester resin,
[0055] Epoxy resin E12 20 parts;
[0056] 6 parts of curing agent,
[0057] 0.5 parts of benzoin,
[0058] 4 parts of leveling agent,
[0059] Mn and Zn co-doped copper molybdate 3 parts;
[0060] 5 parts of KH-550 modified molybdenum sulfide;
[0061] The preparation method of the KH-550 modified molybdenum sulfide comprises the following steps:
[0062] Dissolve 1 mol of potassium molybdate and 5 mol of thiourea in 200 mL of deionized water and stir to obtain a mixed solution; then hydrothermally react at 240°C for 15 hours, wash, and vacuum dry at 90°C for 8 hours to obtain molybdenum sulfide; ultrasonically disperse 100 g of molybdenum sulfide and 15 g of KH-550 in 250 mL of deionized water, and react at 80°C for 2 hours to obtain KH-550-modified molybdenum sulfide.
[0063] The preparation method of Mn and Zn co-doped copper molybdate comprises the following steps:
[0064] 0.04 mol manganese chloride, 0.01 mol zinc acetate, 0.95 mol copper nitrate and 3 mol ammonium molybdate were ultrasonically dispersed in 150 mL deionized water to obtain a dispersion, and then a 0.5 mol / L sodium hydroxide solution was added dropwise to adjust the pH of the dispersion to 9, and then hydrothermally reacted at 160° C. for 4 h, filtered, washed, and dried at 110° C. for 10 h to obtain Mn and Zn co-doped copper molybdate.
[0065] A method for preparing a powder coating, the method comprising the following steps:
[0066] The raw materials are mixed to obtain a mixed material, which is then melt-extruded, tableted and crushed through a twin-screw extruder, and then pulverized and sieved to obtain a powder coating; the temperature of the first zone of the twin-screw extruder is 100° C., the temperature of the second zone is 125° C., the temperature of the third zone is 115° C., and the screw speed is 50 r / min.
[0067] Example 3
[0068] A powder coating, comprising the following components in parts by weight:
[0069] 120 parts of polyester resin,
[0070] Epoxy resin E12 40 parts;
[0071] 2 parts of curing agent,
[0072] 1.5 parts of benzoin,
[0073] 2 parts of leveling agent,
[0074] Mn and Zn co-doped copper molybdate 7 parts;
[0075] 1 part of KH-550 modified molybdenum sulfide;
[0076] The preparation method of the KH-550 modified molybdenum sulfide comprises the following steps:
[0077] Dissolve 1 mol of sodium molybdate and 3 mol of thiourea in 200 mL of deionized water and stir to obtain a mixed solution; then hydrothermally react at 160°C for 30 hours, wash, and vacuum dry at 60°C for 12 hours to obtain molybdenum sulfide; ultrasonically disperse 100 g of molybdenum sulfide and 5 g of KH-550 in 250 mL of deionized water, and react at 50°C for 4 hours to obtain KH-550-modified molybdenum sulfide.
[0078] The preparation method of Mn and Zn co-doped copper molybdate comprises the following steps:
[0079] 0.02 mol manganese acetate, 0.03 mol zinc nitrate, 0.95 mol copper chloride and 1 mol ammonium molybdate were ultrasonically dispersed in 150 mL deionized water to obtain a dispersion, and then a 0.5 mol / L sodium hydroxide solution was added dropwise to adjust the pH of the dispersion to 9, and then hydrothermally reacted at 140° C. for 6 h, filtered, washed, and dried at 90° C. for 18 h to obtain Mn and Zn co-doped copper molybdate.
[0080] A method for preparing a powder coating, the method comprising the following steps:
[0081] The raw materials are mixed to obtain a mixed material, which is then melt-extruded, tableted and crushed through a twin-screw extruder, and then pulverized and sieved to obtain a powder coating; the temperature of the first zone of the twin-screw extruder is 100° C., the temperature of the second zone is 125° C., the temperature of the third zone is 115° C., and the screw speed is 50 r / min.
[0082] Comparative Example 1
[0083] The difference between Comparative Example 1 and Example 1 is that an equal amount of Mn-doped copper molybdate is used to replace Mn and Zn co-doped copper molybdate. The preparation method of Mn-doped copper molybdate comprises the following steps:
[0084] 0.05 mol of manganese nitrate, 0.95 mol of copper acetate and 2 mol of ammonium molybdate were ultrasonically dispersed in 150 mL of deionized water to obtain a dispersion, and then a 0.5 mol / L sodium hydroxide solution was added dropwise to adjust the pH of the dispersion to 9, and then hydrothermally reacted at 150° C. for 5 h, filtered, washed, and dried at 100° C. for 14 h to obtain Mn-doped copper molybdate.
[0085] Comparative Example 2
[0086] The difference between Comparative Example 2 and Example 1 is that an equal amount of molybdenum sulfide is used to replace the KH-550 modified molybdenum sulfide. The preparation method of the molybdenum sulfide comprises the following steps:
[0087] 1 mol of ammonium molybdate and 4 mol of thiourea were dissolved in 200 mL of deionized water and stirred to obtain a mixed solution; then, a hydrothermal reaction was carried out at 200° C. for 20 h, and the mixture was washed and vacuum dried at 80° C. for 10 h to obtain molybdenum sulfide.
[0088] Comparative Example 3
[0089] The difference between Comparative Example 3 and Example 1 is that copper molybdate co-doped with equal amounts of Mn and Zn is used to replace KH-550 modified molybdenum sulfide.
[0090] The performance of Examples 1-3 and Comparative Examples 1-3 was tested, and the specific test results are shown in Table 1. Among them,
[0091] Antibacterial performance test: Tested according to GB / T21866-2008;
[0092] Impact resistance test: Tested according to GB / T1732-1993;
[0093] Wear resistance test: Tested in accordance with GB / T 23988-2009.
[0094] Table 1:
[0095]
[0096] It can be seen from Table 1 that the powder coating prepared by the present invention has excellent antibacterial properties and mechanical properties. Moreover, by comparing Examples 1-3 with Comparative Examples 1-3, it can be seen that the present invention significantly promotes the improvement of antibacterial properties and mechanical properties by adding Mn and Zn co-doped copper molybdate and KH-550 modified molybdenum sulfide to the powder coating.
[0097] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A powder coating, characterized in that: By weight, it includes the following components: 120-160 parts of polyester resin; Epoxy resin E12 20-40 parts; 2 to 6 parts of curing agent; 0.5-1.5 parts of benzoin; 2 to 4 parts of leveling agent; Mn and Zn are co-doped with 3-7 parts of copper molybdate; 1~5 parts of KH-550 modified molybdenum sulfide; The preparation method of the KH-550 modified molybdenum sulfide comprises the following steps: The molybdenum source and thiourea are dissolved in deionized water, and stirred to obtain a mixed solution; then a hydrothermal reaction is carried out, and the mixture is washed and vacuum dried to obtain molybdenum sulfide; the molybdenum sulfide and KH-550 are ultrasonically dispersed in deionized water, and reacted at 50-80°C for 2-4h to obtain KH-550-modified molybdenum sulfide; The molybdenum source includes at least one of sodium molybdate, potassium molybdate or ammonium molybdate; the molar ratio of the molybdenum source to thiourea is 1:3-5; the mass ratio of the molybdenum sulfide to KH-550 is 100:5-15; The hydrothermal reaction conditions are 160-240° C. for 15-30 h, and the vacuum drying is 60-90° C. for 8-12 h. The preparation method of Mn and Zn co-doped copper molybdate comprises the following steps: Ultrasonic dispersion of manganese salt, zinc salt, copper salt and ammonium molybdate in deionized water to obtain a dispersion, then dropwise addition of a 0.5 mol / L sodium hydroxide solution to adjust the pH of the dispersion to 9, followed by hydrothermal reaction, filtration, washing and drying to obtain Mn and Zn co-doped copper molybdate; The manganese salt is one of manganese nitrate, manganese chloride and manganese acetate; the zinc salt is one of zinc nitrate, zinc chloride and zinc acetate; the copper salt is one of copper nitrate, copper chloride and copper acetate; the molar ratio of the manganese salt, zinc salt, copper salt and ammonium molybdate is: x:y:(1-xy):1~3; x=0.02~0.04:; y=0.01~0.03; The hydrothermal reaction is carried out at 140-160° C. for 4-6 hours, and the drying is carried out at 90-110° C. for 10-18 hours.
2. A powder coating according to claim 1, characterized in that: The polyester resin is SJ4868 polyester resin; the curing agent is adipic acid dihydrazide; and the leveling agent is BYK-368P.
3. The method for preparing a powder coating according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: The raw materials are mixed to obtain a mixed material, which is then melt-extruded, tableted and crushed through a twin-screw extruder, and then pulverized and sieved to obtain a powder coating; the temperature of the first zone of the twin-screw extruder is 100° C., the temperature of the second zone is 125° C., the temperature of the third zone is 115° C., and the screw speed is 50 r / min.
4. Use of a powder coating according to any one of claims 1 to 3 in the field of food, medical care or hygiene.
Citation Information
Patent Citations
Nano self-cleaning powder coating and preparation method thereof
CN117165168A
Plasma powder coating with antibacterial function and preparation method thereof
CN118109104A
Weather-resistant powder coating and preparation method thereof
CN118185434A
Waterproof and anticorrosive paint special for marine ships
CN106318105A
Copper molybdate nanoparticle and preparation method and application thereof
CN106904655A